Wednesday

April 23, 2014

April 23, 2014

Posted by **Michelle Summer** on Friday, January 18, 2013 at 9:25pm.

- Algebra -
**Reiny**, Saturday, January 19, 2013 at 12:40amYou must know that

A^3 + B^3 = (A+B)(A^2 - AB + b^2)

so 8x^3 + 27)

= (2x + 3)(4x^2 - 6x + 9)

**Related Questions**

Algebra - Factor out 8x^3y^6 + 27 One factor is 2xy^2+3. (The sum of the cube ...

ALGEBRA - Can someone explain the following to me? 1.How do you factor the ...

algebra - How do you factor the difference of two squares? How do you factor the...

factoring cubes - how to factor x^3-27 well since 27 is a perfect cube and so is...

Algebra - I have been doing sum of cubes and difference of cubes problems and I ...

algebra - how to factor 8x^3+27?

Algebra - Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^...

Algebra - Rewrite the middle term as the sum of two terms and then factor by ...

alegbra - 8x-11 < -27= 8x+11< -27= 8x=ll-27 8x=-16 x=-2 Check this problem...

Algebra 1 - Factor the expression by grouping. 8x^2-3x-8x+3